Analysis of the reasons for the lack of adherence to treatment and methods of their correction in patients with resistant and pseudoresistant arterial hypertension in family doctor practice - Zbitnieva, Viktoriia; Busel, Svitlana (ScienceRise: Medical Science, 2017)
Aim. The analysis of the main reasons for the lack of adherence to treatment in patients with resistant and pseudoresistant arterial hypertension and the possibilities of their elimination by different poor adherence correction methods against the background of antihypertensive therapy optimization in family doctor practice. Methods. Questionnaires and surveys, physical examination, office blood pressure measurement, ECG. Retrospective examination of 120 patients with resistant essential hypertension lasting more than 3 years was carried out. First and foremost, in all patients, a new method for differential diagnostics of resistant and pseudoresistant arterial hypertension by office blood pressure measurement and ECG 3 hours before and after previously assigned three antihypertensive drugs administration was used. According to the differential diagnostics results, the patients were divided into 4 groups: 30 patients with pseudoresistant arterial hypertension and 30 patients with resistant hypertension, having common methods for poor adherence to treatment correction, and 30 patients with pseudoresistant arterial hypertension and 30 patients with resistant hypertension, having additional methods for poor adherence to treatment correction. Results. In most both pseudoresistant and resistant hypertension patients, adherence to treatment violations were found. Conclusion. On the basis of comparative study of different methods for the lack of adherence to treatment correction in patients with resistant and pseudoresistant hypertension, the efficiency of the additional correction methods was scientifically proved, namely: implementation into the patients’ practice of blood pressure home monitoring with keeping a self-control diary and telephone consultation (visits) method, in elimination of subjective reasons, mostly related to irregular intake of remedies in most patients